Catching RNAs on chromatin using hybridization capture methods. (8th November 2017) - Machyna, Martin; Simon, Matthew D
Abstract: The growing appreciation of the importance of long noncoding RNAs (lncRNAs), together with the awareness that some of these RNAs are associated with chromatin, has inspired the development of methods to detect their sites of interaction on a genome-wide scale at high resolution. Hybridization capture methods combine antisense oligonucleotide hybridization with enrichment of RNA from cross-linked chromatin extracts. These techniques have provided insight into lncRNA localization and the interactions of lncRNAs with protein to better understand biological roles of lncRNAs. Here, we review the core principles of hybridization capture methods, focusing on the three most commonly used protocols: capture hybridization analysis of RNA targets (CHART), chromatin isolation by RNA purification (ChIRP) and RNA affinity purification (RAP). We highlight the general principles of these techniques and discuss how differences in experimental procedures present distinct challenges to help researchers using these protocols or, more generally, interpreting the results of hybridization capture experiments.